Feasibility of Home-Use Animal-Assisted Activities in Patients With Implanted Cardiac Electronic Devices: A Pilot Study. (24th February 2016) - Jirak, Peter; Gerger, Daniel; Glenk, Lisa M.; Wegner, Christian; Stöllberger, Claudia
Animal-assisted activities (AAAs) are mainly carried out in institutions. The aim of this prospective pilot study was to assess the willingness of patients with cardiac implanted electronic devices (IEDs) to participate in AAA. The sample included 75 ambulatory patients (18 females, M age = 69 years), who attended an outpatient clinic for control of antibradycardic pacemakers ( n = 15) or implanted cardioverter defibrillators ( n = 60). Twenty-three percent were current and 48% were previous pet-owners. Current pet-owners were younger than non-pet-owners (63.5 vs. 72.0 years, p = .0003). Twelve patients (16%) showed interest in AAA visits. However, only two patients agreed to an AAA visit. Both patients were visited once, but declined further visits. Hence, AAA sessions at home were poorly accepted, mainly because the patients considered themselves too busy or healthy, or due to a general disinterest in AAA. Potential health benefits associated with AAA may not be feasible to investigate during home visits of AAA-teams in patients with IEDs who are healthy enough to leave their homes. For further studies concerning AAA in patients with cardiovascular diseases, we suggest focusing on institutions like rehabilitation centers or day care centers and on more severely sick, homebound patients.